Adult related haematopoietic stem cell donor care: Views of Transplant Nurses. (August 2019) - Zomerdijk, Nienke; Turner, Jane; Hill, Geoffrey R.; Gottlieb, David
Abstract: Purpose: The objective of this mixed-methods study was to explore the experiences and perspectives of Transplant Nurses (TNs) in caring for related donors (RDs). Method: In this mixed-methods study, both quantitative and qualitative data were collected from semi-structured interviews with seven TNs from two clinical hospitals. Closed and multiple-choice questions regarding the organisation of RD care were administered in addition to an in-depth exploration of TN experiences and perspectives of RD care. Interviews were audio-recorded, transcribed, and qualitative data was subjected to thematic analyses. Results: The analysis identified 5 themes relating to RD care: managing complex family dynamics and ambivalence; concerns about RD psychological adjustment; identifying and correcting RD misperceptions; limited guidelines and structured processes; limited training for the role and access to supervision. Five themes were identified describing the barriers to delivering RD care: RDs unwilling to express their concerns; language; time constraints; medical priority of clinicians; biomedical focus of TNs. All TNs agreed they would like additional training in the psychosocial management of RDs. TNs identified key areas for improvement, including psychosocial support and educational material. Conclusions: Our results highlight the significant role of TNs in RD care, and underline issues specific to the current RD care environment. Lack of training for the role and limited guidelines addressing RD care management are key issues which may detrimentally affect RD care. The pivotal role of TNs must be acknowledged and supported by improving TN training and implementing clear guidelines for the management of RDs. The trial has been registered on the publicly accessible register:www.clinicaltrials.gov site with the identifier ACTRN12617000407392. Highlights: Despite the expansion of related donor transplants, guidelines for related donor care management are still lacking. Transplant Nurses are well placed to provide holistic care but report lack of training to respond to challenges. Common challenges include family conflict, donor ambivalence and distress after recipient death. Communication skills training and development of referral pathways to access psychosocial care are needed. Guidelines to promote consistency and strategies for responding to challenges should be a priority.